CORPORATE SOCIAL RESPONSIBILITY, CORPORATE REPUTATION, AND SHARE PRICE: A STUDY OF CONSUMER GOODS INDUSTRIES USING SUSTAINABLE ACCOUNTING STANDARD BOARD (SASB) DISCLOSURES - Juniati Gunawan; Hermawan Susilo (Jurnal Magister Akuntansi Trisakti, 2021)
This study aims to seek theㅤinfluenceㅤof corporateㅤsocialㅤresponsibilityㅤdisclosures (CSRD) on share prices with the company's reputation as intervening variable. The samples are derived from all of the consumer goods industries, which areㅤlistedㅤonㅤIndonesiaㅤStockㅤExchange during 2014-2018. Content analysis method is used to measure the company’s corporate social responsibility disclosures based on company’s annual reports and/or sustainability reports. Unlike previous studies, this research applies the Sustainability Accounting Standard Board (SASB) as the disclosures list to award the scores. Panel regression method and Eviews 9 were applied as analytical tools. Findings shows that CSRD does not influence the corporate reputation, but in contrast, CSRD influence significantly and positively to the share prices, and so does the corporate reputation. However, CSRD does not influence the share prices when it is mediated by the corporate reputation as intervening variable. When CSRD and Reputation were examined together, controlled by ROA, these variables positive significantly influence the corporate share price.